2020
DOI: 10.1111/papr.12925
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Preoperative Pentoxifylline on Postoperative Pain and Development of Secondary Hyperalgesia in Patients Undergoing Laparoscopic Appendectomy: A Randomized, Double‐Blind, Placebo‐Controlled Trial Study

Abstract: BackgroundAfter surgery and loss of anesthetic effect, postoperative pain can annoy the patient and affect patient satisfaction with treatment. This study was aimed at evaluating the effect of preoperative pentoxifylline (PTX) on postoperative pain and development of secondary hyperalgesia in patients undergoing laparoscopic appendectomy (LA).MethodsThis randomized, double‐blind, placebo‐controlled clinical trial study was conducted on 91 eligible subjects with acute appendicitis referred to Shahid Beheshti ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…Nazemi's 109 trial showed a clinically relevant reduction in pain intensity at rest and while coughing using 10 mg kg −1 of pentoxifylline preoperatively in adult patients undergoing laparoscopic appendicectomy. A significantly lower analgesic consumption and no complications attributed to pentoxifylline were reported.…”
Section: Regional Analgesia Techniquesmentioning
confidence: 99%
“…Nazemi's 109 trial showed a clinically relevant reduction in pain intensity at rest and while coughing using 10 mg kg −1 of pentoxifylline preoperatively in adult patients undergoing laparoscopic appendicectomy. A significantly lower analgesic consumption and no complications attributed to pentoxifylline were reported.…”
Section: Regional Analgesia Techniquesmentioning
confidence: 99%